The Effect of Multi-nationality, R&D Costs, and Institutional Ownership on Tax Avoidance - Triyanto, Triyanto; Tarmidi, Deden (Research Horizon, 2024)
This study aims to examine the effect of multi-nationality, research & development costs and institutional ownership on tax avoidance. Manufacturing companies listed on the Indonesia Stock Exchange in the period 2018 to 2023 are the unit of analysis in this study. The purposive sampling method is used to select the appropriate sample, while the multiple regression method is used to analyze the hypothesis on 100 panel data. The results of this study indicate that multi-nationality and research & development costs have no significant effect on tax avoidance, while institutional ownership has a positive effect on tax avoidance. These results contribute to government policy in analyzing taxpayers with institutional share indicators.